Dysregulation of KSHV replication by extracts from Carthamus tinctorius L - Lee, Han; Cho, Hyosun; Son, Myoungki; Sung, Gi-Ho; Lee, Taeho; Lee, Sang-Won; Jung, Yong Woo; Shin, Yu Su; Kang, Hyojeung (The journal of microbiology, 2013)
Carthamus tinctorius L. (CT) is traditionally used to reduce ailments from diseases of the musculoskeletal system and connective tissue and diseases of blood circulation and the cardiovascular system. Flower extracts from CT are known to have antibacterial activity, anti-inflammatory activity, and to inhibit tumor promotion in mouse skin carcinogenesis. In order to discover new antiviral agents from CT extracts, we tested whether CT extracts contain antiviral activity against gammaherpesvirus infection. This study demonstrated that treatment with CT extracts disrupted KSHV latency in the viral-infected host cells, iSLK-BAC16. n-Hexane and EtOH fractions of CT extracts critically affected at least two stages of the KHSV life-cycle by abnormally inducing KSHV lytic reactivation and by severely preventing KSHV virion release from the viral host cells. In addition to the effects on KSHV itself, CT extract treatments induced cellular modifications by dysregulating cell-cycle and producing strong cytotoxicity. This study demonstrated for the first time that CT extracts have antiviral activities that could be applied to development of new anti-gammaherpesviral agents.